AHMED KAMELAFIFI, "HIS BIOGRAPHY, CULTURAL ACTIVITY AND VISION IN BUILDING THE EGYPTIAN ECONOMY UNTIL 1952"HISTORICAL STUDY - Assis. Prof. Dr. Sarmad Akidi Fathi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study dealt with the biography of one of the Egyptian national personalities, which contributed an active role in the modern and contemporary history of Egypt, not only from a political point of view, but also on the cultural, economic and intellectual levels, as it has many talents at all levels. However, she did not take her right to research and study in comparison to some other personalities, as she did not place herself beside the figures who rushed to leadership and search for fame and authority, and this made me study this character.